Model Sifat Kepribadian Memoderasi Hubungan Stres Kerja dan Perilaku Disfungsional Audit - Nikmatuniayah, Nikmatuniayah; Marliyati, Marliyati; Handayani, Jati; Mardiana, Lilis (Universitas Pamulang, 2024)
This study aims to identify personality models that moderate the relationship between work stress and audit dysfunctional behaviour, in an effort to improve audit quality. Specifically, this study aims to investigate the effects of stress and audit dysfunctional behavior, focusing on the role of personality traits namely the big five personality and locus of control. The population of this research is all auditors who work at the Public Accounting Firm in the City of Semarang. The sampling technique uses purposive sampling, namely the sampling technique uses certain criteria. The criteria for the study sample were junior and senior auditor staff who had worked in KAP for at least 1 year, and 57 respondents were obtained. The analysis technique used is moderated regression analysis. Based on the results of data processing it was found that: There was no influence of work stress on dysfunctional behavior; There is no influence of personality traits on the relationship of work stress and audit dysfunctional behaviour. The personality trait in question includes five factors: openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism. The findings also showed that there was no effect of locus of control on the relationship between work stress and audit dysfunctional behaviour. Locus of control is seen from external and internal aspects.